Counseling Guidance Profession In Society - Nabila, Asyifah; Uli Makmun Hasibuan; Yunissa Aristi Anggraina; Tengku Ananda Fitri Syakinah (EDUCATION JOURNAL OF INDONESIA, 2024)
The purpose of writing this article is to find out how the counseling profession works in society. The method the author uses in this research is the library method or literature study. It is hoped that the title of this article can answer people's questions regarding counseling in society. Specifically regarding the implications of the counseling profession in society, namely that it can be done by providing counseling services that are of the nature of a helping profession or social worker. The result of the discussion of this article is that counseling as a community counseling profession is a concept that underlies the role and function of counselors in today's society. In line with the dynamics of life, the need for guidance and counseling is not only felt in the school environment. Currently, counseling services are being developed in broader settings, namely communities that include families, careers, the elderly and other communities, so counseling in society is really needed.Keyword : Profession, Counseling, Society.